Retinal Displacement: Providing New Insights for Retinal Detachment Surgery - Olivier Houle; Eunice You; Mélanie Hébert; Shicheng Jin; Susan Ruyu Qi; Ali Dirani (Journal of Ophthalmology)
Purpose. To review the current literature on retinal displacement and provide a discussion of potential risk factors, postoperative outcomes, and future directions. Methods. Two databases, MEDLINE and EMBASE, were mined using a directed search strategy to identify all articles on retinal displacement. Results. We identified 1522 articles. A total of n = 14 articles were retained. We provide an overview on the potential influence of surgical type (n = 4), tamponade agents (n = 5), postoperative posture (n = 6), and preoperative retinal status (n = 5) on incidence of retinal displacement and visual outcomes (n = 8). Discussion. Pars plana vitrectomy (PPV) with gas tamponade is associated with displacement rates of up to 72%, typically in a downward direction. Meanwhile, pneumatic retinopexy and PPV with silicone oil may offer similar surgical success with a significantly lower risk of displacement. The impact of heavy liquids such as perfluorocarbon liquid, postoperative positioning and preoperative extent of detachment on displacement remains inconclusive. Patients with displacement had a significantly lower visual acuity and higher rates of distortion than those without displacement. However, not all patients with displacement experienced visual symptoms. Conclusion. Retinal displacement is a new concept in our understanding of retinal detachment. Additional studies are needed to better define its impact on postsurgical outcomes.